Analysis of the Role of Corporate Governance in the Design of Financing Projects and Executive Compensation - Nur Amalianty; Muhammad Afdal; Andi Murtafiah (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study explores the role of corporate governance in shaping financing project decisions and executive compensation policies by examining the interconnections among governance mechanisms, financial decision-making, and incentive structures. The research also highlights the significance of transparency, accountability, and sustainability as drivers of organizational resilience and stakeholder trust. Research Method: A systematic literature review (SLR) approach was employed to synthesize findings from recent studies on governance frameworks, financing strategies, and executive compensation. Relevant academic articles from leading journals were selected using specific inclusion criteria, with emphasis on empirical evidence and conceptual advances published after 2018. The review process involved thematic analysis to identify patterns and draw insights across governance configurations in various sectors and regions. Results and Discussion: The findings reveal that independent board structures and risk committees enhance financial decision-making by promoting accountability and risk mitigation. Incorporating ESG (Environmental, Social, and Governance) indicators into executive compensation strengthens stakeholder confidence and fosters long-term sustainability. However, governance effectiveness varies depending on board composition, regulatory environments, and market dynamics. The discussion emphasizes the need for an integrated approach that balances financial performance, risk management, and sustainability objectives. Implications: The study offers practical recommendations to strengthen governance practices, including enhancing the roles of audit and risk committees, improving transparency in financial reporting, and integrating ESG metrics into executive compensation policies. The findings underscore the importance of adaptive governance models that respond to regulatory changes and market demands. Future research should consider comparative and longitudinal analyses to further validate governance frameworks across diverse organizational contexts.